Literature at the barricades : the American writer in the 1930s - Bogardus, Ralph F., 1938-; Hobson, Fred, 1943- (Book collections on Project MUSE., 1982)
This collection captures the sense-at times the ordeal-of the 1930's literary experience in America. Fourteen essayists deal with the experience of being a writer in a time of overwhelming economic depression and political ferment, and thereby illuminate the social, political, intellectual, and aesthetic problems and pressures that characterized the experience of American writers and influenced their works. The essays, as a group, constitute a reevaluation of the American literature of the 1930's. At the same time they support and reinforce certain assumptions about the decade.